Problèmes de définition ou définitions du problème ? La « pornographie » dans « l’affaire Baise-moi » - Damien Simonin (Genre, Sexualité et Société)
Many reactions appear in France as Baise-moi is released in June 2000, namely because it appears as ambivalent regarding distinctions between cinematographic genres, between porn and “traditional” films. Different definitions of pornography and interpretations of the movie are introduced to change its conditions of diffusion, until a new category is introduced to classify movies and regulate their projections.This paper analyzes “the Baise-moi affair” as a public problem about the movie and as the moment for redefining pornography. Coming back to that history enables to show heterogeneous definition’s and classification’s criteria, allies or competing groups in those processes and effects on sex representations and on movies diffusion. Finally, this “affair” does not show what pornography is, but what can be shown and who can show it.